Visual Results of Intravitreal Bevacizumab (Avastin) Treatment for Branch Retinal Vein Occlusion a Multi Center Study - Muhammad Junaid Sethi, Umer Khan, Natasha Junaid, Nazli Gul, Ishan Ullah, Muhammad Israr (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the visual outcomes in patients with branch retinal vein obstruction after intravitreal bevacizumab (Avastin) injection. Study Location and Duration:, Department of Ophthalmology Abaseen hospital and Khyber medical center Peshawar from January 2019 to January 2022 both department conducted this multi-center study. Methodology: Patients with BRVO received at least one intravitreal Bevacizumab (Avastin) injection of 1.25 mg in 0.05 ml. Snellen visual acuity tests, Fundus Fluorescein Angiography (FFA), and Optical Coherence Tomography were used to assess the patients (OCT). A complete eye exam was conducted before treatment began, and monthly follow-up examinations were scheduled for the following six months. Results: The total number of patients and eyes was 78, with a mean age of 60. (SD 15.1). The average number of Intravitreal bevacizumab (Avastin) injections administered to patients was four (SD 1.40) per eye. There were no negative consequences observed. Before treatment, the average central macular thickness was 568 microns, but after three months it was only 370 microns (p0.001), and by six months it had decreased to 290 microns. Three months later, the average acuity was much better than at the start (p=0.001), with log MAR = 0.30 (SD 0.22). During the most recent 6-month follow-up, the mean visual acuity was log MAR = 0.40 (SD 0.23), better than the baseline value (p 0.001). Overall, 44 eyes showed an improvement in their vision. Conclusion: Intravitreal Bevacizumab intravitreally for branch retinal vein occlusion improves vision. Bevacizumab intravitreally enhances visual acuity, macular edema, and ischemia. Bevacizumab reduces the risk of vision-threatening vitreous hemorrhage and neovascularization. Hence, Bevacizumab improves vision and treats branch retinal vein occlusion effectively. Keywords: Intravitreal Bevacizumab (Avastin), Branch Retinal Vein Occlusion (BRVO), Visual Acuity Improvement, Macular Ischemia Relief. Retinal Neovascularization Reduction